2021
DOI: 10.1002/ptr.7116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of propolis plus Hyoscyamus niger L. methanolic extract on clinical symptoms in patients with acute respiratory syndrome suspected to COVID‐19: A clinical trial

Abstract: The outbreak of Coronavirus disease 2019 (COVID-19) has caused a global health crisis. Nevertheless, no antiviral treatment has yet been proven effective for treating COVID-19 and symptomatic supportive cares have been the most common treatment. Therefore, the present study was designed to evaluate the effects of propolis and Hyoscyamus niger L. extract in patients with COVID-19. This randomized clinical trial was conducted on 50 cases referred to Akhavan and Sepehri Clinics, Kashan university of medical scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…1 ). Nine studies were in silico studies [7,8,16,25 − 30], while three studies were case reports or case series [18] , [31] , [32] , and the other three studies were RCTs [17] , [33] , [34] . Of the nine in silico studies, two studies determined the effect of propolis against SARS-CoV-2 angiotensin-converting enzyme 2 (ACE2) [7] , [8] , six studies used SARS-CoV-2 main protease enzyme as the target enzyme [16,25 − 29], two studies used SARS-CoV-2 RNA-dependent RNA polymerase as the target enzyme [16] , [29] , three studies focused on spike protein subunit one [16] , [27] , [30] , and one study focused on spike protein subunit two [25] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Nine studies were in silico studies [7,8,16,25 − 30], while three studies were case reports or case series [18] , [31] , [32] , and the other three studies were RCTs [17] , [33] , [34] . Of the nine in silico studies, two studies determined the effect of propolis against SARS-CoV-2 angiotensin-converting enzyme 2 (ACE2) [7] , [8] , six studies used SARS-CoV-2 main protease enzyme as the target enzyme [16,25 − 29], two studies used SARS-CoV-2 RNA-dependent RNA polymerase as the target enzyme [16] , [29] , three studies focused on spike protein subunit one [16] , [27] , [30] , and one study focused on spike protein subunit two [25] .…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs [17] , [33] , [34] reported the effect of propolis or honey, as an adjuvant to standard care, on clinical symptoms of COVID-19. One study reported the effect of honey with Nigella sativa seeds on time of clinical symptom improvement and time to viral clearance [17] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Propolis has been used therapeutically for centuries as it possesses various biological activities including antimicrobial, anti-inflammatory, anti-cancer, and antioxidant properties [4][5][6]. Several preliminary clinical studies have also demonstrated the efficacy of propolis as an adjuvant for treating Sars Cov-2 infections [7,8]. Therefore, propolis appears to be a promising raw material for the future development of new therapeutic compounds.…”
Section: Introductionmentioning
confidence: 99%